Evaluation of Components of Space Quality in Urban walkways (Case Study: Cultural walkway in Rasht) - Rahimberdi Annamoradnejad; farzaneh Razeghi; Mahmood Arvin (نشریه جغرافیا و برنامه‌ریزی, 2019)
Introduction: The most important public and creative spaces of the city are pedestrian or pedestrian highways that have the highest social role, with full pedestrian dominance, which can form an alley, a market, a market, a path to a square, a park, or the space of a complex, and Be a base for citizens to spend their leisure time. In the context of a spirit-based approach to the central context of the cities, the municipality of Rasht created a walkway in the center of the city. The walkway in the center of the city and its easy access to it has created the right atmosphere for citizens to interact and interact. The formation of such an environment requires the necessary indicators and criteria to attract citizens. Investigating the criteria and indicators affecting this environment and active participation of citizens in improving the quality of this environment and other similar environments is necessary. The purpose of this study was to evaluate the factors affecting the quality of Rasht cultural pedestrian space from the users' point of view.